THEME-BASED TEACHING IN TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS - Nida Mujahidah Fathimah (Journal of English and Education, 2014)
This present study tries to investigate the students’ responses towards theme-based teaching in teaching English vocabulary. This study involved 32 students in the fifth grade of one primary school in Bandung. The methodology used in this study was classroom action research by conducting observation through field notes and questionnaire as the instruments. The findings of this study revealed that students’ responses were highly positive towards the implementation of theme-based teaching. It was shown that theme-based teaching could enhance students’ interest in learning process that was supported by the themes chosen. Moreover, the students also argued that theme-based teaching could improve their vocabulary.